PENGUATAN KEMAMPUAN BERBAHASA INDONESIA SISWA MELALUI PEMBELAJARAN KONTEKSTUAL DALAM PEMBIASAAN INTERAKSI DI KELAS - Yuriananta, Renda; Wardani, Berlian Kusuma; Zahra, Laila Maghfirotul; Bachtiar, Misbakhul Munir; Aldafuadiyah, Nabila Safira; Sipahutar, Rosa Margaretta (Jurusan Pendidikan Bahasa, Fakultas Ilmu Budaya, Universita Brawijaya, 2026)
This article addresses the ongoing need to cultivate the habit of using Indonesian actively, politely, and communicatively during classroom interactions, particularly among lower-grade students with regional language backgrounds. The study aims to describe the implementation of contextual learning—integrated into classroom interaction routines—as a strategy to strengthen students' Indonesian language skills. A descriptive qualitative approach was employed, utilizing data collection techniques such as observation, interviews, and documentation. Research conducted in a first-grade class at SDN Bumiayu 1 revealed that the teacher adapted instructional modules to suit students' abilities, focused on foundational literacy, and utilized active learning methods such as storytelling, singing, educational games, letter and syllable cards, and instructional videos. Instruction was linked to students' real-life experiences and supported by peer tutoring, authentic assessment, individual guidance, and collaboration with parents. These findings demonstrate that contextual learning fosters an active, enjoyable, and meaningful learning environment. Consequently, establishing classroom interaction habits based on contextual learning can progressively strengthen students' Indonesian language proficiency, particularly regarding foundational literacy, confidence in communication, and language use in daily learning activities.